PENERAPAN PENDEKATAN SAINTIFIK TERHADAP KETERAMPILAN MENULIS PANTUN SISWA KELAS VII SMP TERBUKA BUKIT RAYA PEKANBARU - Apriliani, Rini Trisda; Razak, Abdul; Syafrial, Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of the scientific approach to writing skills of pantun vii grade students at smp terbuka bukit raya pekanbaru. The method used is a quantitative research method with an experimental research model. The design of this research is one group secret-postest design. Sampling techniques using simple random sampling. The sample in this study amounted to 52 people in two classes. Data collection techniques are test techniques. Tests are used to assess students' writing skills. Data analysis techniques used the liliefors normality test, then tested the hypothesis using the wilcoxon test. The results show that there is an influence on the application of the scientific approach to the writing skills of pantun students of vii grade students at smp terbuka bukit raya pekanbaru. Keywords: Scientific Approach, Writing Skills, Pantun